Balanced Phono-Amps An Extension to the 'The Sound of Silence' Editions - Vogel, Burkhard (Springer International Publishing : Imprint: Springer, 2016)
In 12 chapters (Part I) this extension to the two 'The Sound of Silence' editions covers the development, calculation, construction and measurement of the fully differential (= balanced) phono-amp solution 'RIAA Phono-Amp Engine II'. Additionally, the balanced measurement amplifiers & measurement tools, the discussion on BJT gain stages, the 1/f noise calculation methods for BJTs, the calculation of fully-differential amplifiers, the numerous Mathcad worksheets, and the presentation of test and calibration records fill a further 10 chapters of Part II with essential knowhow that will equip the reader to develop his/her own phono-amp solution in the most balanced way - and of course, as low-noise as possible. Engine II offers eight different amplifying paths from the Engine's input to its output - solid-state as well as valve driven. To expand the input possibilities via an additional external input, any kind of other linear input amplifiers can be connected. Further, a selection of six highly diverse external input amplifier examples are discussed - BJT, valve, transformer and JFET-driven variants. Although the book primarily focuses on MC cartridge amplification, MM cartridge considerations are not neglected: two further chapters in Part II address methods for increasing the signal-to-noise ratios of MM phono-amps.  .